The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.3758/s13420-017-0298-6
|View full text |Cite
|
Sign up to set email alerts
|

Measuring the “transfer of meaning” through members of equivalence classes merged via a class-specific reinforcement procedure

Abstract: Seven participants received conditional discrimination training that established the 12 conditional relations A1B1, A2B2, A3B3, A1C1, A2C2, A3C3, D1E1, D2E2, D3E3, D1F1, D2F2, and D3F3. The A stimuli were pictures of faces portraying emotional expressions; the others were arbitrary forms. Correct responses resulted in presentations of class-specific reinforcers, Sr1, Sr2, and Sr3. After training, tests confirmed the formation of ABC and DEF equivalence classes. Further tests then documented the merger of the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
5
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 40 publications
2
5
0
1
Order By: Relevance
“…We know that when CS and US categories consist of nonsense words and emotional faces respectively, valence transformations appear limited by nodal distance. Specifically, valences for CS that are two or more nodes away from their face US may not significantly transform (Bortoloti and de Rose, 2009; Amd et al., 2018; Silveira et al., 2018). A recent study by Amd et al.…”
Section: Introductionmentioning
confidence: 99%
“…We know that when CS and US categories consist of nonsense words and emotional faces respectively, valence transformations appear limited by nodal distance. Specifically, valences for CS that are two or more nodes away from their face US may not significantly transform (Bortoloti and de Rose, 2009; Amd et al., 2018; Silveira et al., 2018). A recent study by Amd et al.…”
Section: Introductionmentioning
confidence: 99%
“…Some studies have reported that the use of differential outcomes procedure has also been used to test the emergence of equivalence classes (Dube et al 1989;Goyos, 2000;Johnson et al 2014;Minster, Jones, Elliffe, & Muthukumaraswamy, 2006;Monteiro & Barros, 2016;Schenk, 1994;Silveira & de Rose, 2015;Silveira et al 2017;Varella & de Souza, 2014). For example, Dube et al (1989) used food vs. drink as outcomes, Schenk (1994) used red beads vs. blue beads, Goyos (2000) used red tokens vs. yellow tokens that could be exchanged for video cartoons or for small toys, Johnson et al (2014) used tokens with different colors, Monteiro and Barros (2016) used different sounds correlated to each class, Silveira and de Rose (2015) and Silveira et al (2017) correlated specific images and sounds to each class, and Varella and de Souza, (2014) used different edible reinforces and sounds. In their study Silveira and de Rose (2015) did not found the formation of equivalence relations using non-biological outcomes, they explained their results assuming a lack of reinforcing properties of the outcomes used and suggested that nonbiological outcomes were not efficient for reinforcing the behavior of typical adults in laboratory settings.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study we used a MTO matching-to-sample task because represent a more challenging task for the subjects according with the results reported by Estévez et al (2001) and visual vs. auditory outcomes in order to extend the generality of the DOE. This is a novel test of the DOE procedure´ effectiveness and could represent an efficient and cheap way for reinforcing complex human behavior in laboratory settings, in contrast with some studies in which the participants earned points and gift cards as outcomes (Johnson, Meleshkevich, & Dube, 2014;Silveira, Mackay, & de Rose, 2017).…”
mentioning
confidence: 99%
“…Resultados análogos foram reportados em praticamente todos os estudos conduzidos anteriormente (cf. Aggio et al, 2014;Almeida & de Rose, 2015;Bortoloti & de Rose, 2011, Bortoloti et al, 2013Silveira et al 2016;Silveira, Mackay, & de Rose, 2017).…”
Section: Discussão Geralunclassified